Approach for analytical characterization and toxicological assessment of ozonation products in drinking water on the example of acesulfame. (15th April 2019) - Buchner, Eva-Maria; Happel, Oliver; Schmidt, Carsten K.; Scheurer, Marco; Schmutz, Beat; Kramer, Meike; Knauer, Martina; Gartiser, Stefan; Hollert, Henner
Abstract: The monitoring and control of drinking water quality is generally important as it significantly contributes to the health of the population. In this context, particular attention has to be paid to the use of treatment techniques during drinking water treatment. It is known that the formation of reaction products (transformation products) has to be taken into account when oxidizing agents such as ozone are used. Different transformation products are classified as critical to health and require analytical examination. The risk assessment for previously unknown transformation products can be difficult as far as not all transformation products are present as single substances or the individual substances are not present in a sufficient high concentration or cannot be isolated from the original solution. The aim of this work is to show exemplarily the identification and quantification of ozonation products (OPs) after ozonation and their toxicological characterization, using the artificial sweetener acesulfame. It was shown that OPs can be fully characterized using ion chromatography in combination with different detection systems. A major OP could be recovered as a pure substance by crystallization and direct genotoxicological testing was possible without previous enrichment processes. Acesulfame samples of different concentrations in ultrapure and in drinking water after ozonation were tested in several genotoxicity tests. These tests revealed genotoxic effects of acesulfame after ozonation in ultrapure water in several genotoxicological test systems (micronucleus test, umu test, Ames-fluctuation-test and comet assay). In contrast, the crystallized ozonation product OP168 did not show any positive effects. Therefore, it seems likely that the observed effect was caused by the second major product OP170. However, a sufficiently large amount of analytically pure substance OP170 could not be obtained. It was also shown that the rate of the OP170 formation in drinking water is significantly lower than in ultrapure water and that ozonation in drinking water did not induce genotoxic effects. Graphical abstract: Image 1 Highlights: The study shows identification and quantification of ozonation products (OPs). The water treatment like ozone can lead to certain previously unknown risks. The genotoxic effects of ACE in ultrapure water were detected. One of the major OP has a low formation and short stability in drinking water. Holistic and realistic risk assessment of ACE and its OPs with this combination.